Lessons learnt from implementing change in newborn bloodspot screening processes over more than a decade: Midwives, genetics and education. (December 2019) - Nisselle, Amy; Bishop, Michelle; Charles, Taryn; Morrissy, Sally; King, Emily; Metcalfe, Sylvia; Gaff, Clara
Highlights: Midwives play a critical role in helping parents understand newborn screening (NBS) for genetic conditions to make informed decisions. We studied midwives' NBS knowledge and behaviour before and after significant changes to program processes. Midwives consistently stated that it is important for parents to know which conditions are, and are not, screened for in NBS. Midwives' knowledge of process changes improved but knowledge of which conditions are screened decreased for some conditions; these changes aligned with content of educational materials and bloodspot collection cards. Changes to NBS processes need accompanying multifaceted education programs; the bloodspot collection card should be seen as an educational tool, not just a procedural requirement. Abstract: Objective: To explore midwives' roles and education requirements in newborn bloodspot screening (NBS) for genetic conditions, as programs and supporting education evolve over time. Background: NBS processes are evolving and will continue to evolve with new genetic and genomic technologies. Midwives have a critical role in facilitating NBS, as they are the primary healthcare professional to interact with parents at the time of collecting the bloodspot. As new consent processes and genomic technologies are incorporated into NBS, midwives need to stay up-to-date with these changes, so that parents can make an informed decision about having the test and future use of the DNA sample. Research design/setting: We used a cross-sectional approach to analyse midwives' knowledge and behaviour in 2005/6 and 2016, with changes in NBS processes and education introduced in 2011. Findings: We found midwives' NBS knowledge improved in 8/18 areas after a 10-year period, mostly related to process changes, but there was also an increase in misconceptions regarding which conditions are screened. Areas of significant improvement were not consistently explained by participation in continuing professional development (CPD). We found midwives used official brochures and NBS collection cards to guide discussions with families. Changes to the NBS collection cards, together with the content of CPD materials, aligned with the significant improvements and deficits we observed. When considering potential changes to future maternity care that incorporates emerging genomic technologies, midwives indicated the main barrier was their lack of knowledge; the majority (60.3%) reported supervision support to attend genomics CPD. Key conclusions: Changes in NBS practice should be implemented through multifaceted programs that include education sessions and procedural prompts. The NBS collection card should be seen not just as a legal consent document but also as an educational tool. Implications for practice: As NBS programs evolve through the addition of conditions screened for or changes to technology or consent processes, multiple strategies should be applied to upskill midwives to ensure they can best support parents to make informed choices.